2017
DOI: 10.1089/end.2017.0542
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Accessory Pudendal Artery Transection on Erections During Robot-Assisted Radical Prostatectomy

Abstract: Good surgical technique dictates the preservation of APAs. However, when preservation is questioned, we found that APA transection had no measurable effect on recovery of erections or potency regardless of age, preoperative ED, or number of APAs transected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
0
5
0
1
Order By: Relevance
“…Our surgical technique regarding accessory pudendal arteries (APAs) was recently published. 6 While surgical preservation of APAs is optimal, we presented data from a robust patient cohort that sacrifice of APA(s) during RARP did not lessen recovery of erectile function. We found no evidence that transecting one or more APA(s) reduced recovery of erections or potency in normal baseline function of men.…”
Section: Postoperative Carementioning
confidence: 95%
“…Our surgical technique regarding accessory pudendal arteries (APAs) was recently published. 6 While surgical preservation of APAs is optimal, we presented data from a robust patient cohort that sacrifice of APA(s) during RARP did not lessen recovery of erectile function. We found no evidence that transecting one or more APA(s) reduced recovery of erections or potency in normal baseline function of men.…”
Section: Postoperative Carementioning
confidence: 95%
“…Previous studies have confirmed that NVB preservation reduces the incidence of postoperative erectile dysfunction and urinary incontinence (9,18). However, even with preservation of the NVBs, accessory pudendal artery or other structures, and the postoperative use of drugs, such as statins, erectile dysfunction appeared to be uncontrollable (7,18,19). Thus, all the patients enrolled in this study had erectile dysfunction and a lack of desire to engage in sexual activity.…”
Section: Discussionmentioning
confidence: 55%
“…It is of note that there is considerable inter- and intraindividual variability in the vascular anatomy of male patients, such as the occurrence of an accessory or aberrant pudendal arteries (4–75%) ( 68 , 69 ). In a case series with 880 patients who underwent RALP, conducted by Williams et al transection of accessory pudendal arteries did not turn out to be an independent prognostic factor for postoperative erectile dysfunction ( 70 ). Nevertheless, current literature is in agreement that penile blood supply can at least partly originate from accessory pudendal arteries, and thus, attempts to the preservation of these vessels should be performed during radical prostatectomy ( 70 , 71 ).…”
Section: Resultsmentioning
confidence: 99%